Production of coffee char at different carbonization times / Mohamad Irfan Aiman Mohamad Suhaimi - Mohamad Suhaimi, Mohamad Irfan Aiman (2024)
The objective of this research is to verify whether the performance of soil can be improved through the addition of carbonised coffee char. Knowing the optimum temperature and residence time of coffee pyrolysis is necessary to generate the best quality of coffee char for use in soil amendment. Coffee is used as a raw material, pyrolysis is carried out in a furnace, and elemental analysis is carried out in order to identify the content of the coffee at different temperatures and time intervals. Coffee is pyrolysed at 40 minutes with three different temperatures of 400°C, 500°C, and 600°C. For a temperature of 500°C, 60, 40, and 20 minutes are applied at different levels of the pyrolysis process. To know in what time or temperature there is more nitrogen, elemental analysis is carried out.